Perlindungan Hukum Dan Ham Terhadap Perempuan Korban Pemerkosaan Di Indonesia - Syaftiara Alissa Dwitami; Jennever Enjelina Gultom; Dea Agusti Saputri; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Rape cases in Indonesia remain a serious issue that place women in a vulnerable position, both physically and psychologically. Although many national and international legal instruments regulate the protection of sexual violence victims, the actual implementation is often far from effective. This problem is not only related to law enforcement but also involves social stigma and the revictimization experienced by victims. This research aims to analyze the importance of legal and human rights protection for women victims of rape in Indonesia. This study employs normative legal research using statutory, conceptual, and case approaches. The sources of legal materials consist of primary sources in the form of legislation and court decisions, secondary sources including legal doctrines and scholarly opinions, and tertiary sources such as legal dictionaries. The analysis is conducted qualitatively by interpreting legislation, legal theories, and judicial practices. The findings reveal that although both national and international legal instruments exist, including the 2022 Sexual Violence Crimes Law and CEDAW, their implementation has not been fully effective in providing comprehensive protection to victims. This research emphasizes the need for synergy between law enforcement, the government, and society to establish a fair, comprehensive, and victim-oriented protection system that upholds human rights.